Faculty Perspectives on Professional Behaviors in Exercise Science and Kinesiology Education. - Davlin-Pater, Christina (Internet Journal of Allied Health Sciences & Practice, 2024)
Purpose: Professional behaviors are important for success, and many employers expect students to learn these behaviors in their academic programs. This study identified the value faculty place on specific professional behaviors, their views, their behaviors related to teaching and fostering professional behaviors, and the negative behaviors observed in students. It also examined the perceived barriers faculty have to teaching professional behaviors. Method: 100 institutions with exercise science and/or kinesiology undergraduate programs were identified. Public and private institutions from 8 regions of the country were included. An email requesting participation in a survey was sent to 1567 individuals identified as faculty in exercise science/kinesiology programs. The survey consisted of 7 parts; 1) the importance of 13 professional behavior themes, 2) faculty attitudes, beliefs, and opinions on fostering professional behaviors; 3) the frequency of negative behaviors observed in students, 4) identification of professional behaviors taught through direct instruction, 5) methods used in direct instruction, 6) perceptions of barriers to teaching professional behaviors and, 7) demographic questions. Results: All professional behavior themes were viewed as important to faculty, and the majority of respondents (97%) strongly agreed or somewhat agreed that teaching and fostering professional behaviors is an important part of undergraduate exercise science/kinesiology education. Faculty were concerned about negative student behaviors such as failure to meet deadlines, poor verbal and non-verbal communication, and tardiness. The majority of respondents (85%) indicated that they provide direct instruction in critical thinking and problem-solving. Direct instruction was also common for communication (75%), collaboration and teamwork (75%), and knowledgeable and curious (72%). Common barriers to teaching professional behaviors included professional behaviors not being listed in the learning objectives (54%), class size (52%), and course content not related to professional behaviors (39%). Time constraints were noted by 60% of the respondents who wrote in a response. Conclusions: Exercise science and kinesiology faculty appreciate the importance of teaching professional behaviors. Faculty use a variety of direct teaching methods. Barriers to teaching professional behaviors should be examined by each academic department along with strategies to mitigate them.